1974
DOI: 10.3758/bf03333056
|View full text |Cite
|
Sign up to set email alerts
|

Response suppression and facilitation by aversive stimuli following septal lesions in rats: A review and model

Abstract: Evidence concerning the effects of septal damage on the performance of rats in tasks involving shock and frustrative nonreward is reviewed. It is argued that the behavior of rats with septal lesions cannot be understood in terms of either a change in the functional intensity of aversive stimuli or the ability to register contingencies between such stimuli and responding. Rather, the lesion appears to decrease the suppressive property of aversive stimuli while augmenting their facilitative or drive-enhancing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(15 citation statements)
references
References 133 publications
0
15
0
Order By: Relevance
“…This hypothesis is supported by considerable behavioral (Gray, 1975) and psychopharmacological data. It is also supported by the results of experiments in which large septal (Dickinson, 1974;Lubar & Numan, 1973) or hippocampal lesions (Altman, Brunner, & Bayer, 1973) have been studied. Thus, when large, unselective lesions have been used, they have been shown to disinhibit the response suppression produced either by nonreward or by shock.…”
Section: Discussionmentioning
confidence: 58%
“…This hypothesis is supported by considerable behavioral (Gray, 1975) and psychopharmacological data. It is also supported by the results of experiments in which large septal (Dickinson, 1974;Lubar & Numan, 1973) or hippocampal lesions (Altman, Brunner, & Bayer, 1973) have been studied. Thus, when large, unselective lesions have been used, they have been shown to disinhibit the response suppression produced either by nonreward or by shock.…”
Section: Discussionmentioning
confidence: 58%
“…This pattern of results is anticipated by early work examining the effect of septal lesions on punished responding which suggested that aversive stimuli, in addition to punishing effects, also serve to increase the general motivation or behavioural activation of the animals, i.e. they have both aversive and invigorating properties (Dickinson 1974(Dickinson , 1975. The preference for the CP lever under midazolam is therefore the result of the loss of the aversive impact of the CS+, without loss of its invigorating properties.…”
Section: Discussionmentioning
confidence: 62%
“…I have summarized some relevant findings in Table 2. These concern Broadhurst's (1960,1975) selective breeding programme (MNR relative to MR rats are similar to females relative to males: Gray, 1971 b); the effects of anti-anxiety drugs (drugged relative to undrugged animals are similar to females relative to males: Gray, 1977); and the effects of septal lesions (lesioned relative to intact animals are similar to females relative to males : Lubar & Numan, 1973;Dickinson, 1974). Table 2 summarizes a great deal of information.…”
Section: The Explanation Of Sex Differences In the Ratmentioning
confidence: 99%